Hidup dalam Transit: Representasi Diri Digital Pengungsi Muda Oromo di Instagram terhadap Rekonstruksi “Refugeeness” dalam Interaksi antara Pengungsi dan Audiens - Clarisa Irene (Antropologi Indonesia, 2021)
The representation of refugees and asylum seekers should not be bounded to media’s depiction of it. This paper focuses on refugees’ self-representation on Instagram, one of the most used social media platforms in the world, which cannot be understood separately from their daily life as refugees. Drawing from the observation of young Oromo refugees, I find that Instagram—and other social media—are used as a form of online participation to fill their days in transit. Other than offering the Oromo youths access to entertainment and new insights, Instagram also provides a space in which they can build and maintain relationship and it allows them to talk about and for themselves with photos, videos, and captions. They do this by celebrating their mundane moments as well as accessing and expressing happiness through the platform. Their posts also affect the audience or other users who know them as refugees and have online and offline interaction with them. They evoke a peculiar reconstruction of refugeeness. This paper offers a view of refugeeness as something constantly reconstructed and a thorough as well as contextual understanding of the lives of refugees, especially urban refugees who live in a transit country.